Aplikasi Notifikasi Tagihan Penggunaan Air Pelanggan PDAM Kota Makassar Berbasis SMS Gateway Menggunakan Metode FIFO (First In First Out) - Muh. Putra Pratama; Muh. Khaliq Gibran Al-gifari; Ervianti Ervianti; Anna Pertiwi (Department of Electrical Engineering, University of Patria Artha, 2022)
The large number of PDAM Makassar City customers who use drinking water services makes each month have to pay a number of water bills that are the customer's obligation. However, sometimes customers neglect the amount of the bill fee, which will result in swelling of the bill because there is no direct billing information, for example through the SMS Gateway service. This SMS gateway billing application is designed to provide convenience in providing information to customers in the form of the amount of bills each month. This SMS gateway application will process sms with the FIFO (First in First out) method where the first input will be directly processed and sent the first time as well. The sms gateway system is built with three main things, namely Gammu as a server tool, especially SMS Gateway, PHP as programming to create SMS web applications, and MySQL as a database server. The result of this study is an application for water use bills for PDAM Makassar City customers Premises.